Project Based Learning Assisted with Flashcard Media and Mathematics Problem-Solving Ability of Elementary School Students - Ade Dyah Wahyuningtyas; Dian Kusmaharti; Via Yustitia (Program Studi Tadris Matematika IAIN Salatiga, 2023)
The purpose of this research is to find out whether there is an effect of Project-Based Learning assisted by flashcard media influences problem-solving ability in plane figure material for grade II students. This type of research uses quantitative research with experimental methods. The design of this study is a nonequivalent posttest-only control design. The population in this study was all grade II students at SDN Dukuh Menanggal 1/424 Surabaya, which amounted to 72 students. Through random cluster sampling selected samples of class II-A as the experimental class and class II-B as the control class. Data collection techniques in this study are using tests. The data analysis technique used is statistical tests using t-tests. The use of a Project-Based Learning assisted by flashcard media encourages students to become more active in designing a real product, easier for students to understand concepts, makes students interested in learning while playing, and active in answering questions in flashcard media. Based on the research results and discussion, it can be concluded that there is an effect of project-based learning model assisted by flashcard media on the ability to solve problems in plane figure material for grade II students at SDN Dukuh Menanggal 1/424 Surabaya.